Roflumilast: a green signal is yet to come - Lone, Nazir; Oba, Yuji (Journal of Thoracic Disease, 2013)
Chronic obstructive pulmonary disease (COPD) is a disabling disease and prevalent across nations with a huge economic impact. COPD is the third leading cause of death in the United States and will become the third leading cause of death worldwide by 2030. The increasing morbidity and mortality of COPD are a major threat to public health (1,2). Epidemiological evidence has shown that a substantial proportion of COPD mortality and morbidity is related to cardiovascular disease (3-5). Multiple studies have demonstrated that systemic inflammation and release of inflammatory mediators in COPD may potentially mediate its cardiovascular complications (6).